THE LAW DEVELOPMENT IN INDONESIA UNDER SOEKARNO’S PRESIDENCY (1950-1966) AND NEW ORDER REGIME (1966-1990) AND ITS RELEVANCE TO NATIONAL LAW DEVELOPMENT - Sayuti, Ageng Triganda; Simabura, Charles (jfpublisher, 2024)
This research discusses the thoughts of Professor Soetandyo Wignjosoebroto as outlined in the book “Dari Hukum Kolonial ke Hukum Nasional” which discusses the development of socio-political dynamics in the development of law in Indonesia during the period of half a century (1840-1990). This research aims to identify the development of national law during the reign of President Soekarno, the development of national law during the reign of the New Order regime, and the relevance of the development of national law at the beginning of independence to the development of Indonesian law today. This is a normative juiridical research with statutory, case, comparative, and conceptual approach. The findings of this research indicate that the development of national law during the early years of independence was confronted with the desire to form a national law that was independent of colonial law and faced with legal certainty and development. The relevance of the law development at the beginning of independence with the current Indonesian law development suggests that law development cannot be separated from the existing values in the society.